Multi-Physics Field Based Simulation on the Response and Saturation Properties of Hg1-xCdxTe Based Photovoltaic Detectors With Composition Gradients - Jiahui Chen; Wangyong Chen; Linlin Cai; Haifeng Chen; Pengling Yang; Dahui Wang; Manling Shen; Xiangyang Li; Hui Qiao (IEEE Photonics Journal)
In recent years, there has been a growing interest in photovoltaic detectors based on mercury cadmium telluride (Hg1-xCdxTe), owing to their exceptional photoelectric properties. To provide the physical insights into the modulation effects of Cd composition x on Hg1-xCdxTe under strong injection conditions, specifically for MWIR HgCdTe detectors, we conduct the numerical simulations to investigate the coupling effects of optical and electrical fields on detector performance. The Hg1-xCdxTe detectors based on three kinds of coupling directions, namely inverse field (IF), vertical field (VF), and parallel field (PF), are compared in terms of responsivity and saturation threshold to account for the electric field contributions deriving from the compositional gradient and the applied bias voltage under front illumination (FI) and back illumination (BI). The simulations considering the modulation effects suggest that the detector exhibits better photoelectric response characteristics under FI and a higher saturation threshold for the BI case. The IF structure has the best current response at illumination intensities below 20 W/cm2, with the peak responsivity of the nonlinear model exceeding 2.8 A/W. The VF structure has the best current response at illumination intensities above 20 W/cm2 and exhibits the best saturation characteristics, with its saturation threshold consistently above 15 W/cm2, while the PF structure with nonlinear increasing (nInc) compositional gradient exhibits excellent linearity of response under conditions of high illumination intensity. The simulation methods help design and optimize the detectors with the physical understanding according to the specific requirements.